Pengaruh Kompetensi dan Kualiatas Pelayanan Terhadap Loyalitas Pasien dengan Kepuasan Pasien sebagai Variabel Moderasi di UGD RS Bhayangkara Pontianak - Kintan Utami; Wani Devita Gunardi; Eka Desy Purnama (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the influence of medical staff competence and service quality on patient loyalty, with patient satisfaction as a moderating variable. The results indicate that the competence of medical staff, which includes skills, knowledge, technical abilities, communication, and empathy, plays a crucial role in enhancing patient satisfaction and loyalty. Similarly, service quality, encompassing friendliness, timeliness, attention to patient needs, and interaction comfort, significantly influences patient loyalty. The study also reveals that patient satisfaction serves as a key strengthening factor. The influence of medical staff competence and service quality on patient loyalty becomes more effective when patients feel satisfied with the services provided. Conversely, good competence and service quality alone are not sufficient to build loyalty if patient satisfaction is not achieved. Therefore, the combination of medical staff competence, optimal service quality, and patient satisfaction creates a deep and positive experience, which ultimately fosters long-term patient loyalty toward healthcare facilities and providers.